Analysis of genetically diverse macrophages reveals local and domain-wide mechanisms that control transcription factor binding and function - Link, Verena M. (Cell, 2018)
Non-coding genetic variation is a major driver of phenotypic diversity and allows investigation of mechanisms that control gene expression. Here, we systematically investigated the effects of >50 million variations from five strains of mice on mRNA, nascent transcription, transcription start sites and transcription factor binding in resting and activated macrophages. We observed substantial differences associated with distinct molecular pathways. Evaluation of genetic variation provided evidence for roles of ~100 TFs in shaping lineage-determining factor binding. Unexpectedly, a substantial fraction of strain-specific factor binding could not be explained by local mutations. Integration of genomic features with chromatin interaction data provided evidence for hundreds of connected cis-regulatory domains associated with differences in transcription factor binding and gene expression. This system and the >250 data sets establish a substantial new resource for investigation of how genetic variation affects cellular phenotypes.